Using photography to stimulate children’s sense of cultural diversity within international school twinning - Yapici, Haci (2018)
This thesis seeks to define useful conditions for children within primary education to develop greater awareness and understanding of cultural diversity. In order for children to have cultural exchanges, international school twinning practices was considered to be a sensible strategy to underpin this aim. For providing a communicative medium whereby children might have cultural interactions, photography was the other significant mediating resource. In this report, two interventions were described, involving two separate international school twinning projects between Turkey and the UK. The results of Intervention I indicated that despite gentle prompts from a co-participating researcher, and despite an eagerness from the children, there was limited visual sensitivity in reading and interpreting cultural implications in both their own and photographs and those shared between the participating schools. A modest advance towards the conclusion of the first intervention influenced the design of the next intervention. In Intervention II, a new international school project was established with fewer children and with more time allocated by the schools. Inviting the children to participate in preliminary cultural discussions appeared to create a more effective awareness of the cultural connotations in both their own and the shared photographs. Despite the children’s willingness around engaging with images, they remained limited in their reading and production of provocative visual communication. Suggestions are made for strengthening what is judged a worthwhile purpose, with particular emphasis on the need to scaffold the recruitment of semiotic cues in image towards the goal of cross-cultural discussion. This study found that the children’s semiotic reading of images are at a modest level. Considering this exposure of visual images in every aspect of their lives, this study indicates that the children should be provided with more communicative opportunities with images.